The Economics of Building Life Cycle Costing - Stevens, Alan J (School of Architecture, Planning and Geomatics, 2015)
If one is to arrive at a true reflection of the investment potential and total cost of a particular real property investment the appraisal method used must be capable of allowing for the following factors which, although by no means complete, incorporates those aspects which are required to give a valid and meaningful assessment of the investment . 1. Comparisons to be made with alternative investment opportunities 2. Limited life of certain components in a building which may have to be repaired or replaced 3. Comparisons to be made with alternative materials and/or forms of construction 4. The total costs and income generated throughout the effective life of the building including residual value at the expiry of the investment 5. The effect of the time value of money and the impact of inflation 6. Income tax implications 7. Adaptation to the individual characteristics of each specific project Life cycle costing which is essentially similar in concept to costs-in-use or terotechnology, is a sophisticated method of appraisal capable of satisfying the abovementioned needs. It could be defined essentially as: A financial appraisal technique which allows valid comparative evaluation of available alternative possibilities based on time-phased costs over a specific investment period in order to arrive at the optimum economic solution. The purpose of this thesis is to examine the economics of buildings with special reference to life cycle costing in order to illustrate how valid comparisons of alternative construction methods or material selection can be achieved with a view to optimizing total costs.